(untitled) (Journal of Patan Academy of Health Sciences, 2022)
Jaffrey Beall defined predatory journals and created Beall’s list of predatory journals. Predatory journals exploit the open-access model - they are dishonest and lack transparency. Predatory journals fully developed in the years 2013 and 2014. Developing countries like South Asian and African countries with emerging research fields have the majority of authors published in predatory journals. Predatory journals are even found in reputed databases like PubMed, Medline, Scopus, Science Citation Index Expanded (SCIE) database, Emerging Sources Citation Index (ESCI), and EMBASE (Excerpta Medica dataBASE). There are numerous fake profiles in Facebook, LinkedIn, Twitter, WhatsApp, and Google; although they have been timely deleting such fake profiles. Journals must use institutional email addresses to maintain professionalism and quality. Focusing on quantity over quality of research papers, and lack of proper knowledge about predatory journals make new researchers victimized by such journals. This paper aims to provide proper knowledge about predatory journals and deliver useful tips to prevent genuine researchers from getting victimized by such journals. This paper also intends to provide thorough knowledge about fake social media accounts and email addresses used by such journals, and the importance of institutional email addresses.